Direct Oral Anticoagulants in The Treatment Of Acute Venous Thromboembolism in Patients With Obesity: A Systematic Review With Meta-Analysis - Ahad, Abiya (Journal of Biomedicine and Biochemistry, 2023)
DOACs are the anticoagulation drugs of choice. Using nitroglycerin- containing preparations or sublingual glyceryl trinitrate is not permitted in morbidly obese patients. The lack of supporting evidence made it difficult to support the use of these methods. As a result, the International Soci- ety on Thrombosis and Haemostasis did not recommend using antiplatelet drugs for patients who experienced cerebrovascular accidents. Due to the absence of therapeutic monitoring and the need for anticoagulant bridg- ing, the use of direct oral anticoagulants (DOACs) has gained substantial popularity. Few studies have examined their efficacy in people with obe- sity and VTE. It is presently not advised that these medicines be used as first-line treatments due to preliminary subgroup and pharmacokinetic investigations suggesting lower effectiveness in patients with a bodyweight >120 kg or body mass index (BMI) 40 kg per m2. Our study’s primary objective was to evaluate the recurrence of VTE after DOAC treatment in morbidly obese individuals with a VTE diagnosis. A recent study suggests that DOAC use will benefit Parkinson’s disease patients. This paper aimed to systematically review the literature exploring the efficacy and safety of these agents compared to warfarin in treating heart disease in severely obese patients. Accordingly, the international society on thrombosis and haemostasis has forbidden their use in this cohort of patients. There is am- ple evidence for the benefit of DOACs for these purposes. We wanted to learn about the effectiveness and safety issues of novel oral anticoagulants compared to warfarin. A systematic review of PubMed and EMBASE to 01/04/2020. Our analysis of real-world observational data supports the use of DOAC analogues for treating obese patients with a greater body weight ofFIXME>FIXME120 kg and a BMI ofFIXME>FIXME40 kg/m2. This finding helps to address in this cohort the uncertainty associated with the application of DOACs.